HYPOTHESIS TESTING ON STRUCTURAL COMPARATIVE CALIBRATION MODEL - Solano Dávíla, Oiga Lidia (2005)
ABSTRACT.- In this work study statistic inference on comparative calibration model introduced for Barnett [1]. Consider hypothesis testing in structural comparative calibration model presented in Theobald and Mallison [4]. We study hypothesis testing using the model presented for Theobald and Mallison {l4]. Estimates of maximum likelihood are considered and asymptotic test is proposed based in the Wald statistic. Fisher information matrix is presented. An illustration of the methodology is presented with a data set taken from the literature